RANCANG BANGUN SISTEM INFORMASI PENJUALAN PADA TOKO OMG BERBASIS WEB DI KECAMATAN EMPANG KABUPATEN SUMBAWA - Yudi Mulyanto; Fahri Hamdani; Hasmawati (Jurnal Informatika Teknologi dan Sains, 2020)
This study aims to design and build a sales information system at web-based Omg stores in Empang Subdistrict, Sumbawa Regency, which makes it easy for consumers or customers to obtain information on purchasing and ordering products sold by Omg stores and providing convenience in processing product data and reporting reports. . The method used in this study is qualitative and uses qualitative methods and uses the waterfall method as a method of software development. This system is designed and built using the PHP programming language by using MySql as a database. With the existence of this sales information system can facilitate buyers or customers in the process of ordering and buying at the Omg store and can facilitate shop owners in checking product data available on the store through reports provided by the shop admin.